Deletion of the Ca2+ Channel Subunit α2δ3 Differentially Affects Cav2.1 and Cav2.2 Currents in Cultured Spiral Ganglion Neurons Before and After the Onset of Hearing - Stephani, Friederike; Scheuer, Veronika; Eckrich, Tobias; Blum, Kerstin; Wang, Wenying; Obermair, Gerald J.; Engel, Jutta (Frontiers in Cellular Neuroscience, 2019)
Voltage-gated Ca2+ channels are composed of a pore-forming α1 subunit and auxiliary β and α2δ subunits, which modulate Ca2+ current properties and channel trafficking. So far, the partial redundancy and specificity of α1 for α2δ subunits in the CNS have remained largely elusive. Mature spiral ganglion (SG) neurons express α2δ subunit isoforms 1, 2, and 3 and multiple Ca2+ channel subtypes. Differentiation and in-vivo functions of their endbulb of Held synapses, which rely on presynaptic P/Q channels (Lin et al., 2011), require the α2δ3 subunit (Pirone et al., 2014). This led us to hypothesize that P/Q channels may preferentially co-assemble with α2δ3. Using a dissociated primary culture, we analyzed the effects of α2δ3 deletion on somatic Ca2+ currents (ICa) of SG neurons isolated at postnatal day 20 (P20), when the cochlea is regarded to be mature. P/Q currents were the dominating steady-state Ca2+ currents (54 % of total) followed by T-type, L-type, N-type, and R-type currents. Deletion of α2δ3 reduced P/Q and R-type currents by 60 % and 38 %, respectively, whereas L-type, N-type and T-type currents were not altered. A subset of ICa types was also analyzed in SG neurons isolated at P5, i.e. before the onset of hearing (P12). Both L-type and N-type current amplitudes of wildtype SG neurons were larger at P5 compared with P20. Deletion of α2δ3 reduced L-type and N-type currents by 23 % and 44 %, respectively. In contrast, small P/Q currents, which were just being up-regulated at P5, were unaffected by the lack of α2δ3. In summary, α2δ3 regulates amplitudes of L- and N-type currents of immature cultured SG neurons, whereas it regulates P/Q- and R-type currents at P20. Our data indicate a developmental switch from dominating somatic N- to P/Q-type currents in cultured SG neurons. A switch from N- to P/Q-type channels, which has been observed at several central synapses, may also occur at developing endbulbs of Held. In this case, reduction of both neonatal N- (P5) and more mature P/Q-type currents (around/after hearing onset) may contribute to the impaired morphology and function of endbulb synapses in α2δ3-deficient mice.